Effect of Planting Method on Bio-fence Species, Crop Yield and Soil Conservation in Semi-arid Regions of India - Math, S. K. N.; Patil, S. L.; Adhikari, R. N.; Lamani, Vasudev K. (Indian Forester, 2006)
The field studies were conducted at Research Farm of Central Soil and Water Conservation Research and Training Institute, Research Centre, Bellary and in the farmer’s fields in Joladarasi and Chellagurki watersheds of Bellary district of Karnataka during 2000-2003. Survival per cent, height, collar diameter and canopy spread of all the bio-fence species evaluated were higher in ridge planting over flat planting. Among the bio-fence species, Agave sisilana survived better and recorded higher collar diameter over other species. Lower runoff and soil loss was observed in ridge planting than flat planting. Ridge planting reduced runoff by 56.9% and soil loss by 87.4% over flat planting. Agave sisilana and Euphorbia tirucalli were found more efficient in reducing runoff by 34.6% and 31%, soil loss by 61.9 and 48.4% and conserving 16.4 and 12.4% higher soil moisture over control respectively. At research farm, sorghum yield was higher by 37% when planted with Agave sisilana and bengalgram yield was higher by 23% when planted with Euphorbia tirucalli. Grain yield of sorghum, sunflower and bengalgram crops were higher by 22, 42 and 11% respectively in ridge method over flat method of planting. Sorghum, sunflower and bengalgram crops when planted away from bio-fence species (2-4 m) recorded 7.1%, 4.8% and 6.7% higher yields as compared to near to bio-fence (<2 m) species. The performance of Agave sisilana and Euphorbia tirucalli planted in ridge method of planting was better with minimum effect on crop yields with better soil and water conservation.